Interferensi Morfologi Bahasa Bima ke dalam Bahasa Indonesia Pada Proses Belajar Siswa Sekolah Dasar - Yulianti, Eka; Nurwahyuni, Nurwahyuni; Hasan, Hasan; Yusnarti, Mulya; Marlina, Leni; Latifa, Febi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Bilingualism is caused by the familiarity of two languages ​​between the first language and the second language practiced by the community. Bima is the first language that is still strong in the Dompu community so that the use of the second language, namely Indonesian, is non-standard in the teaching process. This research aims to describe morphological interference in the form of single words from the Bima language into Indonesian. This research uses observation and interview techniques. Checking the validity of the findings was carried out using data validation techniques, namely method triangulation and data source triangulation. The analysis technique used involves three stages, 1) data reduction, 2) data presentation, 3) verification. The results of this research indicate that there is morphological interference in the field of single words, namely that in Indonesian students there are non-standard word forms.